First prenatal case of Noonan syndrome with SOS2 mutation: Implications of early diagnosis for genetic counseling. Issue 6 (22nd March 2021) - Gentile, Mattia; Fanelli, Tiziana; Lepri, Francesca Romana; Gentile, Angela; Orsini, Paola; Volpe, Paolo; Novelli, Antonio; Ficarella, Romina
Abstract: RASopathies are a group of syndromes with partially overlapping clinical features caused by germline mutations of the RAS/MAPK signaling pathway genes. The most common disorder is Noonan syndrome (NS; MIM 163950). We report the first prenatal case of NS with SOS2 (NM_006939.4) mutation in a euploid fetus with a severe increase in nuchal translucency (NT > 12 mm). Trio‐based custom next‐generation sequencing detected a de novo heterozygous missense mutation in the SOS2 gene: c.800 T > A (p.Met267Lys). Owing to the marked variable expressivity of NS and the scarcity of SOS2 mutation‐related NS cases reported in the literature, it is difficult to provide appropriate genetic counseling. Several issues such as the best management technique and optimal NT cutoff have been discussed. In addition, in general, the fine balance between the advantages of an early prenatal diagnosis and the challenge of determining if the detected gene variant is pathogenic and, primarily, the stress of the counselees when providing a genetic counseling with limited information on the prenatal phenotype have been discussed. A prenatal path comprising examinations and multidisciplinary counseling is essential to support couples in a shared decision‐making process.